1998
DOI: 10.1046/j.1365-2141.1998.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric identification of candidate normal stem cell populations in CD45‐negative B‐cell precursor acute lymphoblastic leukaemia

Abstract: Summary. CD45-negative B-cell precursor acute lymphoblastic leukaemia (ALL) provides a unique model to study the stem cell compartment in ALL as leukaemic CD34-positive cells, unlike their normal counterparts, do not express CD45. By increasing the number of events analysed to 10 6 , storing only the events in the region of interest (storage gate), using appropriate isotype controls and stringent washing procedures, a flow cytometric protocol was established to characterize rare CD34 þ CD19 ¹ events. In eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 38 publications
(41 reference statements)
1
22
0
Order By: Relevance
“…Flow cytometric investigations showed that primitive progenitor/stem cells have a phenotype that is very distinct from the leukemic clone (10,11). These observations together with molecular analyses in good-prognosis ALL/t(12/21) demonstrating that primitive CD34 + CD19 À do not carry the leukemia-specific chromosomal translocation (12) supported this hypothesis.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Flow cytometric investigations showed that primitive progenitor/stem cells have a phenotype that is very distinct from the leukemic clone (10,11). These observations together with molecular analyses in good-prognosis ALL/t(12/21) demonstrating that primitive CD34 + CD19 À do not carry the leukemia-specific chromosomal translocation (12) supported this hypothesis.…”
Section: Introductionmentioning
confidence: 62%
“…Its expression is an early event in B-cell development (30) directly following DJ H but preceding or simultaneously occurring with VDJ H rearrangement (31). Analysis of immature CD34 + CD19 À cells for expression of CD45, CD117, and CD133 in the bone marrow from children with B-cell precursor ALL showed that these cells have an immunophenotype similar to normal progenitor/stem cells (10,11). Accordingly, these CD34 + CD19 À cells have a similar clonogenicity in myeloid colony assays compared with CD34 + CD19 À cells from normal bone marrow (12).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A possible biological explanation could be the presence of low numbers of BCR-ABL-positive leukemic progenitors with low or absent expression of the CD19 antigen 40 thus escaping the purging procedure.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify and characterize human Ewing tumor cells infiltrating the murine marrow, two-and three-color flow cytometry was performed according to standard procedures (34,35). In short, bone marrow cells were incubated with saturating amounts of FITC-, PE-, and CyChrome-conjugated antibodies for 20 min at room temperature.…”
Section: Ewing Tumor-nod/scid Mouse Modelmentioning
confidence: 99%